Traditional herbal formula Wu-Mei-Wan alleviates TNBS-induced colitis in mice by inhibiting necroptosis through increasing RIPK3 O-GlcNAcylation - Fan Wu; Qingqing Shao; Zhe Cheng; Xinyu Xiong; Ke Fang; Yan Zhao; Ruolan Dong; Lijun Xu; Fuer Lu; Guang Chen (BMC, 2021)
Abstract Background Accumulating evidence indicated that necroptosis plays an essential role in the pathogenesis of inflammatory bowel disease (IBD). The O-linked β-N-acetylglucosaminylation (O-GlcNAcylation) of necroptotic signal molecule receptor-interacting serine-threonine kinase 3 (RIPK3) was reported to exert a protective effect in gut inflammation. Our recent study suggested traditional Chinese herbal formula Wu-Mei-Wan (WMW) as an effective prescription in mouse colitis. However, the potential mechanisms are not fully understood. Considering the crucial role of necroptosis in the pathogenesis of IBD, therefore, this study was designed to explain whether the anti-colitis effect of WMW is mediated by modulating necroptosis and its related mechanisms. Methods The protective effects of WMW on colitis have been determined by detecting colitis mice body weight, disease activity index (DAI), survival rate and colon length. Colonic inflammation was examined by inflammatory cells infiltration and local cytokines levels. After then, we measured the levels of necroptosis and O-GlcNAcylation. C O-immunoprecipitation experiments were used to address whether elevated O-GlcNAcylation can inhibit necroptotic signal transduction in the treatment of WMW. Finally, the key enzymes in O-GlcNAcylation: O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA) were examined and molecular docking analysis was used to determine effective natural compounds in the regulation on OGT and OGA activities. Results Our results showed that WMW significantly improved mice body weight, survival rate and colon length, decreased DAI in TNBS-induced colitis. WMW obviously alleviated colonic inflammatory responses with reduced macrophages, neutrophils infiltration and local IL-1β, IL-6, TNF-α and IFN-γ levels. It was found that WMW increased colonic O-GlcNAcylation level and inhibited the activation of RIPK1, RIPK3 and MLKL. Then, further experiments revealed that WMW enhanced OGT activity and suppressed OGA activity, thereby increasing RIPK3 O-GlcNAcylation and inhibiting the binding of RIPK3 and MLKL, which led to the inhibition of necroptosis. Additionally, docking analysis demonstrated that hesperidin, coptisine and ginsenoside Rb1 may exert a major role in the regulation on OGT and OGA activities by WMW. Conclusion Our work demonstrated that WMW can alleviate TNBS-induced colitis in mice by inhibiting necroptosis through increasing RIPK3 O-GlcNAcylation.